Seed policies and regulatory reforms - Spielman, David J. (International Food Policy Research Institute, 2020)
In this chapter, we explore how policies, programs, and regulations related to seed and genetic resources are evolving across Africa, and whether these changes have the potential to improve farmers’ access to improved cultivars and quality seed. We highlight several signs of progress in seed system development and identify challenges that still lie ahead. We also caution against a one-sizefits- all approach to seed system development and encourage a more thoughtful discourse on the myriad issues influencing the public policies that shape Africa’s seed systems, including the sensitive political economy issues that influence policies and practices in the seed systems and market development.